Critical review on experimental and theoretical studies of elastic properties of wurtzite-structured ZnO nanowires - Vlassov, Sergei; Bocharov, Dmitry; Polyakov, Boris; Vahtrus, Mikk; Šutka, Andris; Oras, Sven; Zadin, Veronika; Kyritsakis, Andreas (De Gruyter, 2023)
In this critical review, we call attention to a widespread problem related to the vast disagreement in elastic moduli values reported by different authors for nanostructures made of the same material. As a particular example, we focus on ZnO nanowires (NWs), which are among the most intensively studied nanomaterials due to their remarkable physical properties and promising applications. Since ZnO NWs possess piezoelectric effects, many applications involve mechanical deformations. Therefore, there are plenty of works dedicated to the mechanical characterization of ZnO NWs using various experimental and computational techniques. Although the most of works consider exactly the same growth direction and wurtzite crystal structure, reported values of Young’s modulus vary drastically from author to author ranging from 20 to 800 GPa. Moreover, both – diameter dependent and independent – Young’s modulus values have been reported. In this work, we give a critical overview and perform a thorough analysis of the available experimental and theoretical works on the mechanical characterization of ZnO NWs in order to find out the most significant sources of errors and to bring out the most trustable results. --//-- This is an open access article S. Vlassov, D. Bocharov, B. Polyakov, M. Vahtrus, A. Šutka, S. Oras, V. Zadin, A. Kyritsakis; Critical review on experimental and theoretical studies of elastic properties of wurtzitestructured ZnO nanowires; Nanotechnol. Rev., 2023, 12, 20220505 (pp. 1-23); DOI: 10.1515/ntrev-2022-0505; https://www.degruyter.com/document/doi/10.1515/ntrev-2022-0505/html published under the CC BY 4.0 licence.
The work was funded by ERA Chair MATTER from the European Union’s Horizon 2020 research and innovation programme under grant agreement No 856705 and by the Latvian Council of Science project “Core-shell nanowire heterostructures of Charge Density Wave materials for optoelectronic applications” No. lzp-2020/1-0261. The Institute of Solid State Physics, University of Latvia, as a Center of Excellence, has received funding from the European Union’s Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, Project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; ZnO nanowires; Young’s modulus; experimental studies; simulations; ab initio; molecular dynamic